"A revista A Família Cristã e o discurso anticomunista (1960-64)" - Rabusky, Silvia Regina Etges (2008)
This study has as a main objective to analyze the manifestations of the catholic anticommunism, published principally in the Magazine A Família Cristã, in the period of 1960-1964. This Magazine began being published in Brazil since 1934, by the inspiration of the Italian Magazine Famiglia Cristiana, where some of the articles came from, and were translated and adapted to the Brazilian reality. The Magazine A Família Cristã had as principal mission the evangelization through the media . It was focused in the family, notably the woman, constituting in its principal reader. The publication of content related to the social and moral values was frequent in the Magazine A Família Cristã and constituted in behaviors patterns which were expected and lined in directresses and values offered doctrinally by the religion. In a historical context in which the cold war ideological directresses prevailed, the periodical magazine as an incisive attack to the communism, according to the magazine it represented a menace to the basic fundaments of the religion. In the context in analysis, the communist menace was something present in the social imaginary and because of it the proposes of repairing the capitalism, many times, sound very radical. However, the positioning of combating the poverty and objection against the current system, adopted by the Catholic Church, had as objective to preserve the population of the communist influence. For that, they required important social economic repairs. This way the base repairs, proposed by the Jango government, were widely supported by the catholic hierarchy, at the CNBB. We observe however, that in the boarded period the Catholic Church didn t adopt a coherent position toward the repairs needs. In this period, three branches of the church were more evident in the interior of the church: the traditionalists, the conservative modernizers and the modernizers. It s believed by the analyses of the articles published by the Magazine A Família Cristã, in the discussed period, that it may be possible to include it in the group of the modernizers, which was the dominant faction in the church in the decade of 1950.